Um território a muitas vozes: tocautoria e outras práticas violonísticas contemporâneas na América Latina - Stanley Levy Nazareno Fernandes (2014)
A commented and anthropologically oriented description of contemporary Latin American guitar practices is presented, in the context of a case study of the Argentinian cities of Paraná and Rosario. The description is limited to the more caracteristic practices of the observed context, focusing on those less known in the academic environment of Brasil. Starting with the deleuze-guattarian concept of territory, a reference frame based on three axis Latin America, Guitar and Contemporary Music is then created to guide the observation of the foremencioned practices. Data was gathered through analisis of tradicional musical objects (scores and recordings), using a specific method developed by the theorist Dante Grela (1985) within the very context observed, and in field work, which included observation (active and participative), interviews (generally demi-structured) and research with bibliographical material and speciaists. The construction of the description and the data analisis system was based on a model built with contribuitions from anthropology (etnographical writing, as discussed by Wagner (2010) and executed by Clastres (2011 and 2012)), sociology (notion of agents, specially non-humans (Latour, 2001 and 2011) and mediations (Latour (2001), Hennion (2002)), musicology (critics of the text-based analisis (Hennion (2002), Cook (2006)) and of the concept of musical work, and the approach to music as a process (Cook, Ibid.)) and from the cultural studies (concept of Hybridism (Canclini, 2008)). The result of the research is a description of the practices, its practicants, of the the interaction of both with the aesthetic objects and with the social cotext, and of the mediations operated by the various agents. This description prioritized the relational aspect between the different elements observed.